2007
DOI: 10.1086/520682
|View full text |Cite
|
Sign up to set email alerts
|

Community-Acquired Recurrent Bacterial Meningitis in Adults

Abstract: Background. Community-acquired recurrent bacterial meningitis in adults is a relatively rare disease. All previous data were derived from small retrospective case series.Methods. We prospectively evaluated episodes of recurrent bacterial meningitis in a nationwide cohort study in The Netherlands.Results. Thirty-four episodes of recurrent bacterial meningitis were identified among 31 patients; 3 patients experienced 2 episodes during the study period. The mean age was 43 years, and 25 (74%) of 34 episodes occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0
9

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 32 publications
5
92
0
9
Order By: Relevance
“…Bacterial meningitis is the major cause of morbidity in children below the age of 5 years. [1] In our study TBM was found to be in the age group of 9 months to 4 years. Study done by Wilson et al found the greatest frequency of TBM cases in children between the ages 1 to 9 years.…”
Section: Discussionsupporting
confidence: 49%
“…Bacterial meningitis is the major cause of morbidity in children below the age of 5 years. [1] In our study TBM was found to be in the age group of 9 months to 4 years. Study done by Wilson et al found the greatest frequency of TBM cases in children between the ages 1 to 9 years.…”
Section: Discussionsupporting
confidence: 49%
“…Recurrent bacterial meningitis accounts for 1 to 6% of meningitis cases acquired in the community (4,92,95,303). Conditions associated with recurrent meningitis are age dependent.…”
Section: Recurrent Bacterial Meningitismentioning
confidence: 99%
“…Only five reports comprised more than five patients. [7,13,15,16] In this respect, our study features a comparatively higher number of adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Adriani et al [7] have conducted a prospective study on meningitis patients among the population in the Netherlands and reported this rate as 5%. However, the rate may be lower in children.…”
Section: Discussionmentioning
confidence: 99%